Caracterização de adesivos sintéticos com adição de nanopartículas de sílica como carga de reforço - Costa, Tattiane Gomes (2015)
The purpose of this study was to evaluate the quality of wood-adhesive interface in bonded joints of Pinus spp using urea-formaldehyde and phenolformaldehyde as adhesives, with addition of nanofillers of silica nanoparticles. Two types of nanoSiO4, BINDIZIL 78/900 (S1) and Bindzil 1440 (S3), were used. The S1 nanoSiO4 was 3 nm diameter and consisted of 9% of solids. The S3 was 11 nm diameter and consisted of 41% of solids. Different concentrations of nanoSiO4, ie. 0, 1, 3, 5 and 10% were added to adhesives as ratio of dried mass of the adhesive (w/w). The amount of 250 g of the adhesives ureaformaldehyde and phenol formaldehyde was used, on which concentrations of nanoSiO4 were added. These materials were mixed for 10 minutes using mechanical stirring at 1000 rpm. The adhesive and nanoparticles were characterized by means of viscosity analyses, solid content, pH and gel time (only for adhesives). The wood-adhesive interface of bonded joints was analyzed using a light microscope. The silica nanoparticles dispersion was studied by scanning electron microscopy associated with energy dispersive x-ray microscopy. Adhesives containing nanofillers were chemically characterized by means of TG and DSC thermal analyses. Results show that the addition of low concentrations of S3 silica nanoparticles increases the adhesive viscosity, causes decrease of solids content and pH. Besides, there was an upward trend in the gel time period. The TG and DSC were used to investigate cure reactions, and it was found that the cure temperature of the adhesive is slightly affected by the nanoparticles addition.